2021
DOI: 10.1094/pdis-09-20-1912-re
|View full text |Cite
|
Sign up to set email alerts
|

A New Colletotrichum Species Associated with Brown Blight Disease on Camellia sinensis

Abstract: Brown blight, as the most damaging and common foliar disease of tea plant [Camellia sinensis (L.) O. Kuntze] in China, has been recently reported to be caused by different species of the genus Colletotrichum. During the years 2016–2017, tea plants in commercial tea cultivation areas of Chongqing city that reported significant incidences of brown blight disease were investigated and then analyzed using both morphological characteristics and multi-locus phylogenetic analysis. The results showed that at least fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…However, few studies have centered on the metabolite changes in tea plants due to pathogen infection. Colletotrichum , which causes brown blight disease, is the most common pathogen occurring in tea plants, severely affecting the growth of the tea plant [ 24 , 25 ]. Wang et al [ 10 ] found that the levels of (−)-epigallocatechin gallate (EGCG), (+)-catechin (C) and caffeine were induced in C. fructicola -resistant leaf tissues.…”
Section: Resultsmentioning
confidence: 99%
“…However, few studies have centered on the metabolite changes in tea plants due to pathogen infection. Colletotrichum , which causes brown blight disease, is the most common pathogen occurring in tea plants, severely affecting the growth of the tea plant [ 24 , 25 ]. Wang et al [ 10 ] found that the levels of (−)-epigallocatechin gallate (EGCG), (+)-catechin (C) and caffeine were induced in C. fructicola -resistant leaf tissues.…”
Section: Resultsmentioning
confidence: 99%
“…The purified PCR products are sequenced for phylogenetic tree construction and analysis of multilocus gene sequences (Wang, Hao, et al, 2016). For morphological confirmation, colony, conidia, conidiophores, and appressoria characteristics are recorded and determined using methods described by Cai et al (2009) (Chen et al, 2017;Guo et al, 2014;Liu et al, 2015;Shi et al, 2018;Wan et al, 2021;Zhang et al, 2021). Of these species, C. gloeosporioides complex, C. camelliae, and C. fructicola were the dominant species causing anthracnose in C. sinensis (Zhang et al, 2021).…”
Section: The Causative Agent Of Tea Plant Anthracnosementioning
confidence: 99%
“…Using multigene molecular phylogenetic analysis coupled with morphological characterization, a total of 10 well‐characterized species ( C. acutatum , C. alienum , C. boninense , C. camelliae , C. cliviae , C. fioriniae , C. fructicola , C. gloeosporioides , C. karstii , C. siamense ), three new record species ( C. aenigma , C. endophytica , C. truncatum ), four novel species ( C. chongqingense , C. henanense , C. jiangxiense, C. wuxiense ), and one unidentified strain ( Colletotrichum sp.) have been found to cause tea plant anthracnose in China (Chen et al, 2017; Guo et al, 2014; Liu et al, 2015; Shi et al, 2018; Wan et al, 2021; Zhang et al, 2021). Of these species, C. gloeosporioides complex, C. camelliae , and C. fructicola were the dominant species causing anthracnose in C. sinensis (Zhang et al, 2021).…”
Section: Identification and Pathogenicity Of Colletotrichum Spp In Te...mentioning
confidence: 99%
“…Many microorganisms, such as pathogenic and endophytic fungi, bacteria and viruses, live in tea plants (Gao et al, 2016). Diseases caused by pathogenic fungi, such as tea leaf blight caused by Colletotrichum and tea blister blight caused by Exobasidium vexans , are commonly studied in tea plants (Mohktar & Nagao, 2019; Wan et al, 2021). Interestingly, several recent results demonstrated that plant endophytes can inhibit the growth of pathogenic fungi by secreting a large number of metabolites, thereby helping plants by inducing disease resistance (Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many microorganisms, such as pathogenic and endophytic fungi, bacteria and viruses, live in tea plants (Gao et al, 2016). Diseases caused by pathogenic fungi, such as tea leaf blight caused by Colletotrichum and tea blister blight caused by Exobasidium vexans, are commonly studied in tea plants (Mohktar & Nagao, 2019;Wan et al, 2021). Interestingly,…”
mentioning
confidence: 99%